A DNA‐Encoded Chemical Library Incorporating Elements of Natural Macrocycles. Issue 28 (6th June 2019) - Stress, Cedric J.; Sauter, Basilius; Schneider, Lukas A.; Sharpe, Timothy; Gillingham, Dennis
Abstract: Here we show a seven‐step chemical synthesis of a DNA‐encoded macrocycle library (DEML) on DNA. Inspired by polyketide and mixed peptide‐polyketide natural products, the library was designed to incorporate rich backbone diversity. Achieving this diversity, however, comes at the cost of the custom synthesis of bifunctional building block libraries. This study outlines the importance of careful retrosynthetic design in DNA‐encoded libraries, while revealing areas where new DNA synthetic methods are needed. Abstract : Making millions : Inspired by polyketide and mixed peptide‐polyketide natural products, a DNA‐encoded macrocycle library with rich backbone diversity has been developed. The library comprises millions of members and provides a low micromolar binder in a protein selection against the human serum protein AGP. DE=diversity element, BB=building blocks.